EFEKTIVITAS FORMULASI SEDIAAN LOTION DARI EKSTRAK ETANOL DAUN ALPUKAT (PERSEA AMERICANA MILL) SEBAGAI PELEMBAB KULIT - Novasari, Hastrina; Pratiwi, Asti; Mahmiara, Nopri (Jurnal FARMASIMED (JFM), 2021)
Avocado plant can be formulated into a lotion because preparation based on previous research avocado leavescontain high antioxidant is represented with flavonoid compound. The purpose of this study is to know avocado leaves can be formulated into the preparation of lotion and to know the preparation of lotion from extract etanol avocado leavescan moisturaize the skin. The research uses exsperimental method. Avocado leaves is exstrach by maceration process. Exanination of lotion preparation by this research is phytochemical screening test, pH test,irritation test and skin moisturaise test with concentration 3% and 5%. Extrach ethanol avocado leaves can be formulated into a skin moisturaizing lotion preparation with irritation test results showed no irritation on the skin, skin moisture examination result concentration 5% moist. The result showed that moisturaizing lotion preparation from avocado leaves ethanol extrach (Persea americana Mill) for skin moisture with different concentration can be formulated into skin moisturaizing lotion preparation